Analysis of the Distribution of Inheritance to Heirs Based on Legal Status and Replacement in the Civil Code - Anzalika putri Ramadani; Nuranisa; Yolanda Hendartin Batubara; Muhammad Arifin (ISNU Sumatera Utara, 2025)
This study discusses the distribution of inheritance to heirs based on legal status and replacement in Civil Law. The purpose of this study is to analyze the inheritance distribution procedure that is fair and in accordance with applicable legal provisions, as well as to understand the role of replacement heirs in the process. The method used is a normative approach by referring to Articles 841-848 of the Civil Code (KUHPerdata) which regulate the placement of heirs. The results of the study indicate that the distribution of inheritance that does not pay attention to the status and rights of heirs can trigger conflicts between them. Therefore, it is important to follow legal provisions to create justice and legal certainty for all parties involved in the distribution of inheritance.